2015
DOI: 10.1016/j.jastp.2015.10.010
|View full text |Cite
|
Sign up to set email alerts
|

A terrestrial gamma-ray flash recorded at the Lightning Observatory in Gainesville, Florida

Abstract: 2016-12-23T18:44:59

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 18 publications
5
67
1
Order By: Relevance
“…While astronomical satellites in near‐Earth orbits routinely detect TGFs beamed upward, on‐ground facilities have also detected similar phenomena but beamed downward, called downward TGFs. They have been observed with rocket‐triggered (Dwyer et al, ; Hare et al, ) and natural lightning discharges (Abbasi et al, , ; Colalillo, ; Dwyer et al, ; Tran et al, ). In particular, downward TGFs during winter thunderstorms are sometimes bright enough to produce a number of neutrons via photonuclear reactions (Babich, , ) close to the ground; thus, the neutrons and their byproducts can be observed by sea level measurements (Bowers et al, ; Enoto et al, ; Wada et al, , ).…”
Section: Introductionmentioning
confidence: 96%
“…While astronomical satellites in near‐Earth orbits routinely detect TGFs beamed upward, on‐ground facilities have also detected similar phenomena but beamed downward, called downward TGFs. They have been observed with rocket‐triggered (Dwyer et al, ; Hare et al, ) and natural lightning discharges (Abbasi et al, , ; Colalillo, ; Dwyer et al, ; Tran et al, ). In particular, downward TGFs during winter thunderstorms are sometimes bright enough to produce a number of neutrons via photonuclear reactions (Babich, , ) close to the ground; thus, the neutrons and their byproducts can be observed by sea level measurements (Bowers et al, ; Enoto et al, ; Wada et al, , ).…”
Section: Introductionmentioning
confidence: 96%
“…They are one of the highest-energy natural photon emissions on Earth, but the mechanism for creating 10 17 to 10 18 high-energy electrons in the source region [Dwyer and Smith, 2005;Cummer et al, 2014] still remains unclear [Dwyer, 2012;Pasko, 2014]. At present, almost all of the thousands of reported TGFs have been detected by spaced-based gamma ray photon detectors [Fishman et al, 1994;Smith et al, 2005;Briggs et al, 2010;Marisaldi et al, 2010] (four TGF photon observations at ground level [Dwyer et al, 2004Tran et al, 2015;Hare et al, 2016] and one by aircraft have been reported). Ground-based gamma ray photon observations from TGFs are inherently challenging due to the strong atmospheric gamma ray attenuation from the low-altitude atmosphere, and the geometry-driven short horizontal detection range (a few kilometers on the ground), in contrast to a few hundred kilometers in low-altitude orbit.…”
Section: Introductionmentioning
confidence: 99%
“…One TGF was associated with a 2003 classically triggered lightning flash [ Dwyer et al , ], and the other followed a return stroke in a natural cloud‐to‐ground flash in 2009 [ Dwyer et al , ]. A third ground‐level TGF was detected by the Lightning Observatory in Gainesville, FL, in 2015 [ Tran et al , ]. Here we report on a fourth TGF, one that was associated with an altitude‐triggered flash at the ICLRT on 15 August 2014.…”
Section: Introductionmentioning
confidence: 99%